The prognostic and therapeutic value of the tumor microenvironment and immune checkpoints in pancreatic neuroendocrine neoplasms - Zhijiang Chen; Shizhao Lin; Feihong Liang; Zelin Hou; Yuanyuan Yang; Heguang Huang; Yu Pan (Scientific Reports, 2024)
Abstract Pancreatic neuroendocrine neoplasms (Pan-NEN) represent a group of highly heterogeneous cancers, characterized by complex and diverse biological behavior. The objective of this study was to systematically investigate the immunological features of the tumor microenvironment (TME) in Pan-NEN, aiming to identify prognostic biomarkers and explore the therapeutic potential of immunotherapy for Pan-NEN. Tumor and adjacent normal tissues were collected from 56 patients with Pan-NEN. Immunohistochemical analysis was conducted on tumor tissues using a panel of monoclonal antibodies targeting key immune markers. The expression levels of these markers were quantitatively assessed and correlated with clinicopathological features and overall survival. Low expression of CD3, CD8, CD4, CD68, CD163, Foxp3, CD56, CD69, GZMB, HLA-1, HLA-II, PD-1, and PD-L1 were observed in the majority of Pan-NEN patient samples. PD-1 expression was positively correlated with CD4 and Foxp3 expression, while PD-L1 expression was positively correlated with CD68, CD163, and Foxp3 expression; HLA-II expression was positively correlated with GZMB expression. Infiltration of lymphocytes (CD3 + or CD8+) and macrophages (CD68 + or CD163+) and expression of PD-1/PD-L1 were more pronounced in poorly differentiated neuroendocrine carcinoma (Pan-NEC) compared to well-differentiated neuroendocrine tumors (Pan-NET), while CD68 and PD-L1 correlated with advanced disease stage. Conversely, HLA-I antigen expression was commonly downregulated in Pan-NEC. Univariate Cox proportional hazard analysis demonstrated that tumor grade, stage; CD4+, CD68+, and CD163 + cell count; and expression of PD-1 and PD-L1 were significantly associated with poor survival outcomes, while the positive expression of HLA-I was correlated with a more favorable survival prognosis. Furthermore, multivariate Cox proportional hazard analyses revealed that tumor grade, stage, and PD-1 expression are independent prognostic factors. The immunological landscape of Pan-NEN offers potential prognostic value and therapeutic targets. The findings suggest that immunotherapy, particularly targeting the PD-1/PD-L1 pathway, may serve as a promising strategy for the treatment of Pan-NEN, especially for Pan-NEC patients.